PENERAPAN METODE FUZZY PADA PENILAIAN KINERJA KARYAWAN (STUDI KASUS PT. INDOVISUALJAKARTA) - Eka Octavia; Andika Bayu Hasta Yanto Yanto (Jurnal Techno Nusa Mandiri, 2014)
The quality of human resources is required to improve the productivity performance of a company, the human resources that have expertise or competence will be able to improve employee performance. Employee performance appraisal must be conducted to determine the absolute performance of each employee to be achieved. The purpose of this paper is to know How to organize the processing of employee data into a valid consideration and more efficiently by using fuzzy Simple Additive weighting. Assessment of employee performance at PT. Indovisual with some including assessment criteria in terms of knowledge or education and assessment in terms of mental or behavioral using Fuzzy Simple Additive weighting algorithm can work well and can generate analysis and accurate information and faster compared to manual calculation so that PT. Indovisual can use it as a tool for effective decision making and efficient.